Cue Consistency Associated with Physical Activity Automaticity and Behavior - Pimm, R.; Vandelanotte, C.; Rhodes, R.; Short, C.; Duncan, M.; Rebar, Amanda (Routledge, 2016)
© 2015, Copyright © Taylor & Francis Group, LLC. Physical activity is partly regulated by automatic processes such as habits (ie, well-learned responses to cues), but it remains unclear what cues trigger these processes. This study examined the relations of physical activity automaticity and behavior with the consistency of people, activity, routine, location, time, and mood cues present upon initiation of physical activity behavior. Australian adults (N = 1,244, 627 female, M age = 55 years) reported their physical activity automaticity, behavior, and the degree of consistency of these cues each time they start a physical activity behavior. Multiple regression models, which accounted for gender and age, revealed that more consistent routine and mood cues were linked to more physical activity automaticity; whereas more consistent time and people cues were linked to more physical activity behavior. Interventions may more effectively translate into long-lasting physical activity habits if they draw people's attention to the salient cues of time, people, routine, and mood.